The Role of Digital Financial Intelligence in the Economic Resilience of MSME Actors Post-Crisis - Abin, Mohammad; Taufik, Mohammad; Zaenuddin, Ahmad (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
On the one hand, amid the digital transformation of the financial sector, opportunities have increased for Micro, Small, and Medium Enterprises (MSMEs); on the other hand, challenges remain in technology adaptation and sustainable financial management, especially in a post-crisis era. Thus, given the ongoing push toward strengthening economic resilience, an urgent need arises to examine how far digital financial intelligence may act as a key for the survival and growth of MSMEs. The focus of this study is to examine the impact of digital financial intelligence-the financial literacy, attitude toward financial technology, and capability to use digital financial applications-on MSME economic resilience. Data were collected for the survey using a quantitative approach, which consisted of an online questionnaire administered to 220 MSME actors in Indonesia, who were digital financial services users for a minimum of one year. Participants were selected based on purposive sampling, while data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS) supported by SPSS, Tableau, and MonkeyLearn. The results of the analysis reveal that all dimensions of digital financial intelligence have a significant relationship with economic resilience, particularly in the tactile domains of crisis adaptation, recovery, and strategic decision-making. Overall, these results now show life documents the need for greater emphasis on literacy and digital readiness as the bedrock of MSME sustainability. This academic contribution is theoretically developing an integrated model of technology and finance while practically implementing the policy implications that would strengthen an inclusive and adaptive MSME digital ecosystem.